The Bible, the Trump Presidency and the Politics of Exegesis. Issue 1 (27th July 2022) - Friesen, Courtney J P
Abstract : The presidency of Donald Trump exposed and amplified dynamics long active in American religion. Although the overwhelming support of evangelical Christians took many by surprise due to his unconventional religious qualifications, scholars have increasingly established that this political alliance reflects numerous well-established commitments. Accordingly, this study analyses the function of the Bible in the rhetoric of Trump's Christian supporters. Among those surveyed, fundamentalist assumptions of biblical authority and inerrancy are held in common even while the exegetical techniques deployed diverge widely from the corresponding principles of "literal" interpretation and "original" meanings. Their tendencies are rather towards divinatory, even quasi-magical, appropriations of scriptural excerpts, practices attested in antiquity though less well known in American Christianity. For these political apologists, the Bible's status approaches that of a ritual icon possessing spiritual power and conferring authority and legitimacy on those who wield it.